Implementasi Komunikasi Konseling Dalam Meningkatkan Semangat Beragama Pemuda - Wildan Welastiko; Ahmad Sayuti Malik; Dika Sahputra; Hasnun Jauhari Ritonga (EduInovasi: Journal of Basic Educational Studies, 2023)
This research aims to find out the implementation of communication counseling in raising the religious spirit of young people. This study is a qualitative descriptive field study. (field research). Data sources in this study include primary data and secondary data. Data collection techniques in this study include semi-structured interviews, non-participant observations, and documentation. Data analysis techniques in this study include data reduction, data presentation, and conclusions. The results of this study show that the implementation of communication counseling in raising the religious spirit of young people has several benefits. Through counseling communication, young people can understand and appreciate their religious beliefs, maintain a religious spirit, explore the meaning and relevance of religion in daily life, gain guidance and support, encourage personal growth and development, and enhance religious knowledge and skills. Communication counseling creates a supportive environment, facilitates deeper understanding, and helps young people overcome challenges and doubts, so that they can maintain a religious spirit and integrate it into everyday life more meaningfully. Keywords: Implementation of Communication Counseling, Religious Spirit, Youth